Green Growth Opportunities for the Decarbonization Goal for Chile : Report on the Macroeconomic Effects of Implementing Climate Change Mitigation Policies in Chile 2020 - Antosiewicz, Mareck; Gonzáles Carrasco, Luis E.; Lewandowski, Piotr; de la Maza Greene, Nicolás (World Bank, Washington, DC, 2020)
The study presents the results of model simulations showing the macroeconomic effects of the implementation of key climate change mitigation policies in Chile, aimed to reduce CO2eq emissions in accordance with Chilean latest NDC and a target of zero net CO2eq emissions by 2050. By using a multi-sector macroeconomic general equilibrium model, the study shows that the implementation of the proposed policy package could have an overall positive impact on the economy both in the short and long run, as measured by the effect on economic indicators such as GDP, and ensures decoupling of growth from fossil fuel use. Per the analysis, the expected level of GDP by 2050 could increase up to 4,4 percent when compared to the baseline scenario, which corresponds to a higher rate of growth of 0.13 p.p. Main contribution to GDP is expected from increased private consumption and investment, with an estimated 2.4 and 1.7 percent respectively. Since positive economic and financial implications could arise from the implementation of the proposed mitigation package, the unsolicited participation of the private sector could be expected and enhanced. Remaining questions and discussions from the study relate to limitations for the uptake of mitigation measures sooner than long term scenarios. The study evaluated the macroeconomic impact of implementing a mitigation package aligned with the achievement of the recent updated Chilean NDC and committed zero net CO2eq emissions by 2050.